THE EFFECT OF SALES GROWTH, FIRM SIZE, PROFITABILITY, BUSINESS RISK ON CAPITAL STRUCTURE - Valencia, Valencia; Dermawan, Elizabeth Sugiarto (International Journal of Application on Economics and Business, 2024)
The purpose of this research is to determine the effect of sales growth, firm size, profitability, and business risk on capital structure of consumer non cyclicals sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. There are 196 data used as samples which were taken from 71 consumer non-cyclical companies listed on Indonesia Stock Exchange (IDX) for three years in a row. Data used for this reseach is secondary data which is the annual reports from 2020-2022. This research uses multiple regression analysis and helped by Microsoft Excel and SPSS program version 25. Refering to signaling theory, assumption in this research that are used as hypotheses in this study are Sales growth has a significant negative effect on capital structure, Firm size has a significant positive effect on capital structure, profitability has a significant negative effect on capital structure, and business risk has a significant negative effect on capital structure. The results of this study find that sales growth influences capital structure positively, firm size influences capital structure positively. However, profitability influences capital structure negatively. Meanwhile business risk no influences on capital structure.